Harmonic Wave in Disturbed System of Periodic Elastic Layers - Wesołowski, Z. (Engineering Transactions, 1997)
The system of elastic layers periodic in space is considered. One extra cell situated between the cells of numbers k and k + 1 disturbs the system. Harmonic wave of frequency w propagates across the layers. The transparency of the system is defined as the ratio of the transmitted energy flux to the incident energy flux. Transparency depends on the position of the extra layer. The analytic expression for the transparency is given. Transparency is a periodic function of the position of the extra cell, and in general, a non-periodic function of ω. Assuming that the probability of finding the extra layer at the position k is given, the average transparency and its standard deviation has been calculated.